2019
DOI: 10.1080/15348458.2019.1667239
|View full text |Cite
|
Sign up to set email alerts
|

Translating Teacher Funds of Identity into Curricular Proposals for the EFL Classroom: A Model for Student-Teacher Innovation and Professional Development

Abstract: This article describes the progress and findings of a research project, organized in the context of a university Masters course in Teaching English as a Foreign Language (TEFL), which aimed at translating the student-teachers' (STs) funds of identity into worthwhile curricular proposals for the English as a Foreign Language (EFL) subject. The first part of the research involved 38 STs in three workshops through which they became aware of their own funds of identity, expanded their own teacher identity, and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…FoI scholars have developed a fully elaborated, substantial, and theoretically grounded approach that has the potential to make a substantial contribution to countering deficit thinking and achieving schooling that is culturally inclusive within our superdiverse societies. It remains productive in generating empirical research (e.g., Oikonomidoy & Karam, 2020; Villacañas de Castro, 2020; Zhang-Yu et al, 2020; Zhu, 2020). We also note that outside the “niche” of the FoI and FoK conceptual framework, several studies addressed questions related to making education more relevant for students through making learning more personally meaningful (Chaffey, 2018; Hedges, 2018; Silseth, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…FoI scholars have developed a fully elaborated, substantial, and theoretically grounded approach that has the potential to make a substantial contribution to countering deficit thinking and achieving schooling that is culturally inclusive within our superdiverse societies. It remains productive in generating empirical research (e.g., Oikonomidoy & Karam, 2020; Villacañas de Castro, 2020; Zhang-Yu et al, 2020; Zhu, 2020). We also note that outside the “niche” of the FoI and FoK conceptual framework, several studies addressed questions related to making education more relevant for students through making learning more personally meaningful (Chaffey, 2018; Hedges, 2018; Silseth, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, Esteban‐Guitart’s (2014) definition and classification of funds of identity is operationalized to describe the resources that student‐teachers deploy to construct their professional identity as teachers of English. In IELTE programs, the context of this study, understanding student‐teachers’ funds of identity over time can help institutions recognize the motivations (Yuan & Zhang, 2017), knowledge, and skills that future teachers develop to enrich their pedagogical repertoire (Villacañas de Castro, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Supporting student‐teachers’ reflection on their identity may lead to the development of a critical attitude toward curriculum, their own agency as a teacher, and language teaching strategies. For example, a few studies have demonstrated that by enabling student‐teachers to interrogate their beliefs, they deploy resources and frames of thinking and action that may contribute to (1) localizing the curriculum, (2) seeing themselves as agents of change (e.g., Abednia, 2012; Alfaro, 2019; Brown & Heck, 2018), and (3) leveraging their own funds of identity to create lessons that allow learners to identify their own funds while learning English (e.g., Villacañas de Castro, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative teaching models, based on the transmission and memorization of information, have been rethought and contradicted by collaboration and dialogue among students and between students and teachers. Thus, the teacher is no longer the holder of knowledge and the student is no longer seen as a blank sheet, ready to absorb all the information transmitted (Freire, 2014; Acar and Tuncdogan, 2019; De Castro, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%